THE INCLUSION OF CHILDREN WITH ADHD IN EARLY CHILDHOOD EDUCATION (International Seven Journal of Multidisciplinary, 2025)
This article addresses the inclusion of children with Attention Deficit Hyperactivity Disorder (ADHD) in Early Childhood Education, highlighting the challenges and potential of this process. Through a literature review, we analyzed the current conditions of pedagogical practice, teacher training, school environment organization, relationships with families, and public policies related to inclusion. The results indicate that, despite legal support, the effective implementation of inclusion still faces significant obstacles, especially regarding teacher preparation and the structure of educational institutions. Initial and ongoing teacher training is highlighted as essential for understanding the characteristics of ADHD and for adopting differentiated pedagogical strategies that promote children's learning and participation. Furthermore, curricular flexibility, the use of playful and technological resources, as well as the creation of a welcoming and predictable environment, are factors that contribute to the development of these students' potential. The connection between school, family, and multidisciplinary professionals emerges as an essential element in promoting comprehensive support for children with ADHD. It also highlights the importance of combating stigma and misinformation, which still permeate the school environment, hindering full inclusion. Finally, the study concludes that the inclusion of children with ADHD in early childhood education requires a collective and ongoing commitment, involving cultural change, investment in training and infrastructure, and the recognition of diversity as a central principle of education. This way, it is possible to build more fair and equitable educational practices that respect the uniqueness of each child.